Developing a Pocket Dictionary of Arabic Research Terminology for Students in the Arabic Language Education Department - Rizka Utami; Ahmad Nurul Huda Salmas (Al-Muyassar: Journal of Arabic Education, 2025)
The heterogeneity of research terms in Arabic and the absence of a standard reference dictionary have posed significant challenges for Arabic Language Education students in understanding research concepts and composing scientific papers in Arabic. This study aims to develop and validate a pocket dictionary of Arabic research terms to improve the quality of academic writing. This study uses a Research and Development (R&D) approach based on the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The product was developed through systematic identification of research-related terms sourced from research methodology textbooks, scientific articles, student theses, and consultations with experts. Expert validation involved experts in the field of educational materials and media. Data collection used a questionnaire technique. The results of the study showed an overall validation score from material and media experts reached 96.8%, indicating that the product has a very high level of validity and can be used as a reference. In detail, material validity reached 96.6% and media validity reached 96.9%. This research terminology dictionary can be used as a learning resource in research methodology and academic writing courses in the Arabic Language Education study program. This research contributes to strengthening Arabic academic literacy by providing a standard terminology reference source that supports students' research competencies and encourages consistent use of Arabic scientific terms in higher education